A fluorescence-switchable carbon dot for the reversible turn-on sensing of molecular oxygen. Issue 12 (15th March 2021) - Zhao, Yanmin; Geng, Xin; Shi, Xinxin; Guo, Yifei; Sun, Yuanqiang; Qu, Lingbo; Li, Zhaohui
Abstract : CDs were used as a reversible probe for the fluorescence turn-on detection of molecular oxygen. These CDs possessed a short time towards oxygen. The developed CDs can be processed into safety ink and oxygen sensor test strips. Abstract : Developing optical oxygen-sensitive nanoparticles with good biocompatibility and low cost to rapidly detect molecular oxygen in a signal turn-on mode is highly desirable. Herein, we present a phenylenediamine-derived carbon dot (CD), which has been found to display a fluorescence-switchable property, with fluorescence quenching by Na2 S2 O4 and fluorescence recovery triggered by O2 . Because of this unique property, we directly employed the quenched CDs as a reversible probe for the fluorescence turn-on detection of molecular oxygen and found that this detection mode possessed a short response time of 12 s and high sensitivity. Moreover, this CD solution could be used as a writeable ink for the patterning of paper strips and security service without any loss in the fluorescence-switchable property. We thus achieved CD-based test strips for oxygen detection in vacuum packaging. This study not only provides a convenient, low-cost and practical way for oxygen detection but also reveals a fluorescence-switchable CD that will find its applications in numerous O2 -involved fields.